Cross-Cultural Differences and Their Impact on Organizational Culture in International Companies Operating in Malaysia: A Delphi Study - Ng, Shavonne; Wider, Walton; Thet, Khine Zar Zar; Wang, Annie; Ab. Jamil, Nasyra; Hao, Shuwen (Journal of Ecohumanism, 2024)
This research investigates the impact of cross-cultural differences on organizational culture in international companies operating in Malaysia, where diverse cultural backgrounds create unique challenges and opportunities for integration. This study identifies the factors influencing cross-cultural differences and ranks these factors according to their significance within the organizational culture. A two-round Delphi method was employed to collect insights from a panel of 30 experts from international companies in Malaysia. Purposive sampling ensured diverse managerial and non-managerial perspectives. In the first round, an open-ended questionnaire identified key dimensions of cross-cultural impact, and in the second round, experts ranked these dimensions. The data was analyzed to establish consensus and verified through Kendall’s coefficient of Concordance. The study identified seven critical cross-cultural dimensions impacting organizational culture: communication style, leadership and management style, work-life balance, cultural customs and traditions, employee relationships and interactions, cultural adaptation and training, and technology and communication. Communication style and leadership approach were ranked as the most influential factors, highlighting the importance of effective communication and adaptable leadership in diverse cultural settings. This study offers a structured approach to addressing cross-cultural differences in international organizations, with specific focus on Malaysia’s multicultural business environment. The study provides actionable insights for managers to improve integration and align organizational practices with cultural sensitivities by ranking these factors. This research contributes to the limited literature on cross-cultural management in Malaysia and offers a framework that can be adapted for diverse, multicultural settings.